Teacher Strategy in Teaching English During Covid-19 Pandemic for the Eighth Grade Students at SMP Baitul Arqom Balung - Shalahuddin, Aklil; Devanti, Yeni Mardiyana; Nurkamilah, Nurkamilah (Indonesian Journal Publisher, 2024)
Corona virus, also known as COVID-19, has been causing havoc around the world since the end of 2019. The pandemic situation has completely replaced the way of teaching English method from face-to-face learning into online teaching. This research aims to investigate the teachers’ strategies in using online learning platform and the challenges in implementing their strategies during Covid-19 pandemic through online learning platforms